IMPROVING THE AUDIT OF TAX OBLIGATIONS IN COMMERCIAL BANKS - Djumamuratov Sadaddin Khudoybergenovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses the theoretical foundations of the organization of audit in commercial banks. In particular, issues such as the purpose and objectives of the tax liability audit, the risks assessed in relation to tax liabilities and the auditor's actions in relation to them are discussed. It also proposes to improve the tax liability audit based on international auditing standards.